In vitro somatic embryogenesis of superior clones of robusta coffee from Lampung, Indonesia: Effect of genotypes and callus induction media - dwi hapsoro; rahmadyah hamiranti; yusnita yusnita (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hapsoro D, Hamiranti R, Yusnita Y. 2020. In vitro somatic embryogenesis of superior clones of robusta coffee from Lampung, Indonesia: Effect of genotypes and callus induction media. Biodiversitas 21: 3811-3817. This study aimed to investigate the effects of genotypes and primary callus induction media on somatic embryogenesis of superior robusta coffee clones of Lampung. Leaf explants of clones Tugusari, Komari, Tugino, and Wanto were cultured on two types of primary callus induction media (PCIM). PCIM1 consisted of half-strength MS salts, 30 gL-1 sucrose, added with (mgL-1) 0.1 thiamine-HCl, 0.5 nicotinic acids, 0.5 pyridoxine-HCl, 100 Myo-inositol, 200 ascorbic acids, 150 citric acids, and 1 benzyl adenine. PCIM2 consisted of NPCM salts, 30 gL-1 sucrose, added with (mgL-1) 15 thiamine-HCl, 1 nicotinic acid, 1 pyridoxine-HCl, 2 glycines, 130 Myo-inositol, 200 ascorbic acids, 150 citric acids, 1 2,4-dichlorophenoxyacetic acid, and 2 thidiazuron. The highest percentage (100%) of primary callus formation was found in Komari and Wanto clones. PCIM2 resulted in more primary calli than PCIM1. When subcultured to embryogenic callus induction medium, primary calli of clone Komari and Wanto developed into a high percentage of embryogenic calli, while those of the other two turned brown and died. PCIM2-derived primary calli developed into more embryogenic calli. When subcultured on somatic embryo (SE) regeneration medium, these calli underwent the formation of SE of various stages. When subcultured to plant regeneration medium, these SEs developed into plantlets.